Correlation Between Self-Care And Quality Of Life In Patients With Type 2 Diabetes Mellitus At Royal Prima General Hospital Medan - Sartika, Dewi; Ginting, Chrismis Novalinda; Silaen, Mangatas (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2017)
Self-care plays a crucial role in managing Type 2 Diabetes Mellitus (T2DM) and directly impacts patients' quality of life. This study aims to analyze the correlation between self-care and the quality of life of T2DM patients at Royal Prima General Hospital, Medan. This research employs a cross-sectional design with a sample size of [insert number] patients, selected through [sampling method]. Data were collected using standardized self-care and quality of life questionnaires. The results indicate a significant positive correlation between self-care and quality of life, with a p-value < 0.05. Patients who demonstrated better self-care practices reported higher quality of life scores. These findings suggest that enhancing self-care behaviors through education and support programs can improve the overall well-being of T2DM patients.